A method for promoting the degradation of lignocellulose raw materials using a MoS2-activated persulfate catalytic system.

CN116355977BActive Publication Date: 2026-11-03HENAN AGRICULTURAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310584534.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-23
Publication Date
2026-11-03
Estimated Expiration
2043-05-23

AI Technical Summary

Technical Problem

Existing lignocellulose pretreatment technologies suffer from problems such as long reaction times, low efficiency, high costs, and pollutant release. In particular, the persulfate advanced oxidation technology requires high concentrations and enzyme additions during the degradation of crop cellulose, which is difficult to meet practical applications.

Method used

The persulfate catalytic system was activated by MoS2. MoS2 and persulfate were mixed and dissolved in water to form a mixed solution for the pretreatment of lignocellulose. The treatment time and enzyme loading were optimized under the conditions to improve the efficiency of sulfate free radical generation.

Benefits of technology

High-efficiency enzymatic hydrolysis of lignocellulose was achieved with low-dose persulfate and enzyme loading, reducing costs and avoiding the shortcomings of traditional methods, thus providing a green, economical and efficient pretreatment process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present application belongs to the technical field of lignocellulose raw material pretreatment, and particularly relates to a method for promoting degradation of lignocellulose raw material by using a MoS2 activated persulfate catalytic system. The present application improves the production efficiency of sulfate radicals by activating persulfate with MoS2, and proposes a MoS2 activated persulfate catalytic system for pretreatment of lignocellulose. The method for promoting degradation of lignocellulose raw material by using the MoS2 activated persulfate catalytic system has high enzymatic hydrolysis efficiency under low dosage of persulfate and cellulase. The test results of the present application show that MoS2 is a high-efficiency sulfate radical activator, which has high generation efficiency of SO4 ‑ . It not only has excellent performance, but also has very high enzymatic hydrolysis efficiency of more than 90% under the conditions of low dosage of persulfate and low dosage of enzyme loading for 2 h reaction, and does not need to adjust pH again.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lignocellulose raw material pretreatment technology, specifically relating to a method for promoting the degradation of lignocellulose raw materials by utilizing a MoS2-activated persulfate catalytic system. Background Technology

[0002] Due to the non-renewable nature of fossil fuels, they can no longer meet the world's growing energy demand. As an alternative to fossil fuels, biofuels are a promising green raw material. First-generation biofuels mainly include crops such as barley, wheat, corn, and sugarcane.

[0003] As a major agricultural country, China generates a large amount of agricultural waste every year, such as corn stalks, wheat stalks, rice straw, sugarcane bagasse, cotton stalks, and bamboo. Direct burning of agricultural waste leads to serious environmental pollution, while returning it to the fields causes soil pests and diseases, and water and fertilizer runoff. At the same time, a large amount of crop stalks are also an important biomass source for biofuel production. However, due to a lack of appropriate treatment methods, more than half of the corn stalks remain unused; some are used for animal feed, while others are burned in the open, resulting in low conversion rates. Furthermore, these informal practices of disposing of corn stalks often release pollutants into the atmosphere and have a negative impact on the local environment.

[0004] Corn stalks, as a typical agricultural waste resource, are inexpensive, abundant, and have broad application prospects. However, the natural nature and complex internal composition of corn stalks limit their reuse and transformation. Experiments have shown that pretreatment can break down the stubborn structure of lignocellulose, remove some lignin and hemicellulose, and improve the enzymatic hydrolysis efficiency of carbohydrates. Therefore, pretreatment before processing is an essential step to overcome its stubbornness and improve bioconversion rate.

[0005] Common pretreatment techniques, including grinding, alkali treatment, acid treatment, organic solvent treatment, high temperature treatment, and steam explosion, mainly decompose the dense structure of lignocellulose by depolymerizing the lignin and hemicellulose matrix. However, these methods all have some drawbacks, such as long reaction time, low efficiency, and high cost.

[0006] In recent years, the advanced oxidation technology of persulfate has attracted widespread discussion and attention. Persulfate is solid at room temperature, easy to store and transport, highly stable, inexpensive, and readily soluble in water. Through simple heating, the persulfate anion generates sulfate ions. During the thermal activation process, the peroxide bonds in the persulfate molecule undergo a cleavage reaction, forming sulfate radicals (SO42-). -Persulfate oxidation, through oxidation, disrupts the structure of biomass, thereby altering its crystallinity and surface characteristics (Seo, Yeong, Hwan, et al. Lipid extraction from microalgae cell using persulfate-based oxidation[J]. Bioresource Technology: Biomass, Bioenergy, Biowastes, Conversion Technologies, Biotransformations, Production Technologies, 2016, 200: 1073-1075.). In the degradation of crop cellulose, persulfate pretreatment can promote the decomposition of agricultural straw biomass structure, facilitating the degradation of lignin cellulose. Furthermore, persulfate advanced oxidation technology offers advantages such as low cost, no iron-based sludge production during the reaction, no involvement of hazardous compounds, and ease of storage and transportation, making it an ideal green oxidative pretreatment method to easily replace hydroxyl radicals.

[0007] Activation by high temperature alone is far from sufficient, and its disadvantages are also relatively obvious. The required persulfate concentration is too high, and when degrading crops, the amount of enzyme added needs to be increased. Moreover, the digestibility is low, making it difficult to meet its practical application.

[0008] MoS2 has been extensively studied in many fields, including catalysis, due to its strong electron mobility. Its surface possesses numerous active sites, enabling Mo... 2+ Oxidized to Mo 4+ and Mo 6+ This is the reason why it has strong co-catalytic performance.

[0009] Based on this, the inventors activated persulfate with MoS2 to promote the generation of more sulfate free radicals, and used it as a pretreatment for the degradation of lignocellulose in crops, thereby further improving the enzymatic hydrolysis efficiency of lignocellulose. Summary of the Invention

[0010] This invention addresses the technical problems existing in the prior art by utilizing MoS2 to activate persulfate, thereby increasing the concentration of sulfate free radicals (SO4). - To improve production efficiency, a method using MoS2 to activate persulfate catalytic system for the pretreatment of lignocellulose was proposed.

[0011] This invention also proposes a method for promoting the degradation of lignocellulose raw materials by activating a persulfate catalytic system with MoS2. This method still has high enzymatic hydrolysis efficiency even at low doses of persulfate and cellulase.

[0012] To achieve the above objectives, the present invention adopts the following technical solution:

[0013] A MoS2-activated persulfate catalytic system, comprising MoS2 and persulfate, wherein the degradation efficiency of lignocellulose raw materials is improved by activating persulfate with MoS2.

[0014] Specifically, the catalytic system is prepared by mixing MoS2 and persulfate and dissolving them in water to obtain a mixed solution (used as a pretreatment solution). The final concentration of MoS2 in the mixed solution is 0.5-1.5 g / L, the final concentration of persulfate is 1-16 mM, and the pH value of the catalytic system is 2-5, preferably 3.

[0015] Specifically, the final concentration of MoS2 in the mixed solution is 0.5, 0.75, 1, 1.25 or 1.5 g / L, preferably 1.25 g / L; the final concentration of persulfate in the mixed solution is 1, 4, 8, 12, 14 or 16 mM, preferably 14 mM.

[0016] Specifically, when using the catalytic system to pretreat lignocellulose, the final concentration of MoS2 in the mixed solution prepared from MoS2 and persulfate is 1.25 g / L, and the final concentration of persulfate is 14 mM.

[0017] Specifically, the persulfate is one of sodium persulfate, potassium persulfate, ammonium persulfate, and potassium peroxymonosulfate.

[0018] Based on a general inventive concept, this invention also proposes the application of the MoS2-activated persulfate catalytic system in the pretreatment of lignocellulose raw materials.

[0019] Furthermore, the present invention also proposes a method for pretreating lignocellulosic raw materials using the aforementioned MoS2-activated persulfate catalytic system, comprising the following steps:

[0020] MoS2 and persulfate are mixed and dissolved in water to obtain a mixed solution, which is used as a pretreatment solution (MoS2 and persulfate can be mixed in solid form or in solution form). Lignocellulose raw material is weighed and added to the mixed solution. The treatment time is 30 min to 3 h and the treatment temperature is 80-140℃ to obtain the product.

[0021] Preferably, the processing time is 30 min, 1 h, 2 h or 3 h; the processing temperature is 80℃, 100℃, 120℃ or 140℃.

[0022] Specifically, when adding lignocellulose raw materials, add them according to a material-to-liquid ratio of 1g:10-30mL.

[0023] Specifically, the volume of the mixed solution is 100-300 mL, preferably 100 mL.

[0024] Specifically, the final concentration of MoS2 in the mixed solution is 0.5-1.5 g / L, and the final concentration of persulfate is 1-16 mM.

[0025] Specifically, the final concentration of MoS2 in the mixed solution is 0.5, 0.75, 1, 1.25 or 1.5 g / L, preferably 1.25 g / L; the final concentration of persulfate in the mixed solution is 1, 4, 8, 12, 14 or 16 mM, preferably 14 mM.

[0026] Preferably, the lignocellulose raw material is wood or crop straw; more preferably, the wood raw material is eucalyptus, beech, pine, birch or poplar; the crop straw is corn straw, wheat straw, sorghum straw, cotton straw or sugarcane bagasse.

[0027] Based on a general inventive concept, this invention also proposes the application of the MoS2-activated persulfate catalytic system in promoting the degradation of lignocellulose raw materials.

[0028] Furthermore, the present invention also proposes a method for promoting the degradation of lignocellulose raw materials using the MoS2-activated persulfate catalytic system, comprising the following steps:

[0029] (1) Pretreatment: MoS2 and persulfate are mixed and dissolved in water to obtain a mixed solution, which is used as the pretreatment solution. Lignocellulose raw material is weighed and added to the mixed solution. The treatment time is 30 min to 3 h and the treatment temperature is 80-140℃ to obtain the product.

[0030] (2) Enzymatic hydrolysis: The pretreated lignocellulose raw material is added to a buffer solution at a solid-liquid ratio of 1g:10-50mL, and the pH of the buffer solution is 4-6; lignocellulose degrading enzyme is added, and the mixture is enzymatically hydrolyzed at 40-50℃ for 24-120h to obtain the enzymatic hydrolysate; the amount of lignocellulose degrading enzyme added is 5-40FPU / g lignocellulose raw material.

[0031] Specifically, the buffer solution in step (2) is any one of citrate buffer solution and phosphate buffer solution or a mixture of two of them in any proportion.

[0032] Specifically, the volume of the buffer solution in step (2) is 5-25 mL.

[0033] Preferably, the lignocellulose degrading enzyme in step (2) is a complex enzyme composed of any one or more of cellulase, hemicellulase and lignin peroxidase in any proportion; more preferably, the lignocellulose degrading enzyme in step (2) is cellulase.

[0034] Preferably, the pretreatment time of the lignocellulose raw material in step (1) is 30 min, 1 h, 2 h or 3 h, more preferably 2 h; the pretreatment temperature in step (1) is 80℃, 100℃, 120℃ or 140℃.

[0035] Preferably, the pretreatment time of the lignocellulose raw material in step (1) is 2 hours.

[0036] Preferably, in step (2), the solid-liquid ratio of lignocellulose raw material to buffer solution is 1g:10mL.

[0037] Preferably, the enzymatic hydrolysis time of the lignocellulose degrading enzyme in step (2) is 72 h.

[0038] Preferably, the amount of lignocellulose degrading enzyme added in step (2) is 25 FPU / g lignocellulose raw material.

[0039] Furthermore, the enzymatic hydrolysate obtained by the MoS2-activated persulfate catalytic system and the lignocellulose-degrading enzyme treatment in this invention can be used for ethanol fermentation.

[0040] Based on a general inventive concept, this invention also proposes the application of the enzymatic hydrolysate obtained by treatment with the MoS2-activated persulfate catalytic system and lignocellulose-degrading enzyme in improving ethanol fermentation efficiency.

[0041] When applying it, the specific steps are as follows:

[0042] 1) Culture medium preparation: First weigh each component of the culture medium, and then add it to the enzyme hydrolysate to prepare a liquid fermentation culture medium;

[0043] 2) Activation and fermentation of the strain: First, activate the strain, then inoculate it into the liquid fermentation medium in step 1) at an inoculation rate of 5-10% (mass fraction), and incubate it at 30-37℃ for 48-108h to obtain ethanol.

[0044] Specifically, in step 1), the total volume of the liquid fermentation medium is 50-100 mL.

[0045] Specifically, the bacteria used in the ethanol fermentation process are Issatchenkia orientalis HN-1 or Saccharomyces cerevisiae 1308.

[0046] Specifically, the content of each component in the activation medium used in the activation process is as follows: glucose 20g / L, yeast extract 10g / L, and peptone 20g / L.

[0047] Specifically, during the ethanol fermentation process, the content of each component in the culture medium for ethanol fermentation using *Issa mesasula* is as follows: yeast extract 3 g / L, urea 0.2 g / L, peptone 5 g / L, and diammonium hydrogen phosphate 0.1 g / L.

[0048] Specifically, during the ethanol fermentation process, the content of each component in the culture medium used for ethanol fermentation with Saccharomyces cerevisiae is as follows: yeast extract 8g / L, peptone 3g / L, potassium dihydrogen phosphate 7g / L and magnesium sulfate 1g / L.

[0049] Compared with the prior art, the beneficial effects of the method of the present invention are as follows:

[0050] This invention investigated the pretreatment effect of MoS2-activated persulfate on corn straw and optimized the system conditions. The activation mechanism of the system was explored through the study of the structure and physicochemical properties of corn straw. Experimental results showed that MoS2 is a highly efficient sulfate-type activator, effective against SO42-. - The production efficiency of · is very high. It not only exhibits excellent performance, but also achieves extremely high enzymatic hydrolysis efficiency of over 90% after 2 hours of reaction with low doses of persulfate and low enzyme loading, without requiring further pH adjustment.

[0051] This invention optimizes pretreatment process parameters to obtain a pretreatment system with extremely high enzymatic hydrolysis efficiency. The optimal pretreatment conditions for the MoS2-activated Na2S2O8 system are: 14 mmol / L Na2S2O8 added to 1.25 g / L MoS2, treated at 120℃ for 2 h, achieving an enzymatic hydrolysis yield of 93.5% and reducing the enzyme loading to 6 FPU / g, significantly lowering costs for industrial applications. Simultaneously, this pretreatment process avoids the drawbacks of traditional homogeneous Fenton pretreatment, such as long reaction time, generation of iron-based sludge, H2O2 transport problems, and low enzymatic hydrolysis efficiency. It is a green, economical, efficient, and environmentally friendly pretreatment process. This system also provides a newer option for lignocellulose pretreatment processes. Attached Figure Description

[0052] Figure 1 This represents the ratio of single-factor treatment effects when using the MoS2-activated persulfate catalytic system of this invention for pretreatment; wherein, Figure 1 A represents the screening of persulfate species. Figure 1 B represents a comparison of the MoS2-activated persulfate catalytic system, MoS2 pretreatment alone, and persulfate pretreatment alone. Figure 1 C represents the comparison of Na2S2O8 concentration. Figure 1D represents a comparison of Na2S2O8 concentrations. Figure 1 E represents the pH comparison. Figure 1 F represents a comparison of preprocessing times;

[0053] Figure 2 The figure shows the optimization results of enzyme addition based on different solid-liquid ratios; where, Figure 2 a represents a comparison of enzyme addition amounts when the solid-liquid ratio is 1 / 10. Figure 2 b represents a comparison of enzyme addition amounts when the solid-liquid ratio is 1 / 20. Figure 2 c represents a comparison of enzyme addition amounts when the solid-liquid ratio is 1 / 40;

[0054] Figure 3 These are scanning electron microscope (SEM) images of corn stalks before and after pretreatment. Figure 3 a is a scanning electron microscope image of untreated corn stalks; Figure 3 b is a scanning electron microscope image of straw after pretreatment with MoS2-activated Na2S2O8;

[0055] Figure 4 These are FT-IR spectra under different pretreatment conditions; among them, Figure 4 'a' is the unprocessed group. Figure 4 b is the treatment of straw with Na2S2O8 alone. Figure 4 c represents straw treated with MoS2-Na2S2O8 under optimized conditions;

[0056] Figure 5 These are the XRD patterns before and after preprocessing; among them, Figure 5 a represents the XRD pattern of untreated corn stalks. Figure 5 b represents the XRD pattern of corn straw pretreated with MoS2-Na2S2O8 under optimized conditions;

[0057] Figure 6 These are solid-state NMR spectra under different pretreatment conditions; among them, Figure 6 a represents untreated corn stalks; Figure 6 b represents corn stalks pretreated with Na2S2O8 alone; Figure 6 c represents corn stalks pretreated with MoS2-activated Na2S2O8;

[0058] Figure 7 This is a graph showing the ethanol yield of the enzymatic hydrolysate under different pretreatment conditions; among them, Figure 7 a represents the fermentation results of *Issa mesasura*. Figure 7 b represents the fermentation result of the brewing yeast. Detailed Implementation

[0059] The following embodiments are implemented based on the technical solution of the present invention, and provide detailed implementation schemes and specific operation processes. However, the scope of protection of the present invention is not limited to the following embodiments.

[0060] Experimental materials and instruments

[0061] I. Experimental Materials

[0062] 1. Corn stalks (hereinafter referred to as CS) were purchased from Gongyi City, Henan Province. Pretreatment of corn stalks: The purchased corn stalks were crushed to a size of less than 3mm, washed with deionized water to remove lipids and other influencing substances from the raw materials, dried at 65°C to constant weight, and then stored in a desiccator at room temperature to ensure that the composition and structure of the raw materials remained consistent throughout a complete test cycle.

[0063] 2. In this experiment, *Issatchenkia orientalis* HN-1 and *Saccharomyces cerevisiae* 1308 were selected as the test strains, respectively. The above two strains were tested using the methods described in the literature (Fu Chenqing. Study on the effects of nicotine on enzymatic hydrolysis and ethanol fermentation of tobacco stalks [D]. Henan Agricultural University).

[0064] Obtained using the method described in (Learning, 2016.DOI:10.27117 / d.cnki.ghenu.2016.000033.).

[0065] 3. The cellulase used in the examples is a commercial cellulase (Cellic CTec2) purchased from Novozymes (Beijing, China), which is a liquid enzyme preparation.

[0066] 4. The reagents used in the experiment included citric acid, trisodium citrate, persulfates (sodium persulfate, potassium persulfate), antibiotics (2% (w / v) sodium azide solution), MoS2, sulfuric acid (5mM), cellobiose, glucose, xylose, and arabinose. All were analytical grade (AR) and purchased from Sinopharm Chemical Reagent Co., Ltd.

[0067] 5. The citric acid-sodium citrate buffer solution (0.05M, pH=4.8) used is prepared as follows: Solution A: Accurately weigh 21.014g of C6H8O7·H2O into a 500mL beaker, dissolve it with a small amount of deionized water, and then make up to 1000mL to obtain a 0.1mol / L citric acid solution; Solution B: Accurately weigh 29.412g of Na3C6H5O7·2H2O into a 500mL beaker, dissolve it with a small amount of deionized water, and then make up to 1000mL to obtain a 0.1mol / L sodium citrate solution; Take 230mL of Solution A and 270mL of Solution B, mix them thoroughly, transfer them to a 1000mL volumetric flask, make up to 1000mL with deionized water, mix thoroughly, and store in a refrigerator at 4℃.

[0068] 6. pH adjuster: NaOH solution (5 mol / L) is used as the pH adjuster.

[0069] II. Main Instruments and Equipment

[0070] Analytical balance, high-speed refrigerated centrifuge, heated magnetic stirrer, high-performance liquid chromatograph, circulating water vacuum pump, muffle furnace, electric drying oven, scanning electron microscope, X-ray diffractometer, Fourier transform infrared spectrometer, ultrasonic cleaner, etc.

[0071] Example 1

[0072] Example 1 provides a MoS2-activated persulfate lignocellulose pretreatment catalytic system, comprising MoS2 and persulfate, which can improve the degradation efficiency of lignocellulose raw materials by activating persulfate with MoS2.

[0073] The pretreatment catalytic system is prepared by mixing MoS2 and persulfate and dissolving them in water to obtain a mixed solution. The final concentration of MoS2 in the mixed solution is 0.5-1.5 g / L (specifically, for example, 0.5, 0.75, 1, 1.25, 1.5 g / L), and the final concentration of persulfate is 1-16 mM (specifically, for example, 1, 4, 8, 12, 14, 16 mM). Preferably, the final concentration of MoS2 is 1.25 g / L, and the final concentration of persulfate is 14 mM.

[0074] The persulfate is one of sodium persulfate, potassium persulfate, ammonium persulfate, or potassium peroxymonosulfate.

[0075] Example 2

[0076] The method in Example 2 is to add the pretreatment catalytic system from Example 1 to the enzymatic hydrolysis process of corn stalks. This pretreatment catalytic system also has the same degradation effect on wood such as eucalyptus, beech, and pine, as well as crops such as corn, wheat, sorghum, and cotton. In the following examples, the inventors will only use corn stalks as an example to illustrate the effect.

[0077] A method for improving the degradation efficiency of lignocellulose raw materials by pretreatment using a MoS2-activated persulfate system.

[0078] 1 Experimental Methods

[0079] 1.1 MoS2-activated persulfate pretreatment

[0080] First, the types of persulfate were screened to select the one that showed the best combination effect with MoS2. Then, single-factor experiments were conducted to optimize conditions such as persulfate concentration, MoS2 addition, pH value, and pretreatment time by controlling variables. The specific operation process is as follows:

[0081] 1) Prepare a pretreatment solution with different amounts of MoS2 and different concentrations of persulfate solution (Na2S2O8 is used here) to a total volume of 100 mL. The final concentration of MoS2 in the pretreatment solution is 0.5-1.5 g / L, for example, 0.5, 0.75, 1, 1.25, 1.5 g / L, and the final concentration of persulfate is 1-16 mM, for example, 1, 4, 8, 12, 14, 16 mM. Add 5 g of corn straw to the pretreatment solution and fix the solid-liquid ratio (ratio of straw to water) at 1:10. Treat at 120℃ for a certain time (for example, 30 min, 1 h, 2 h or 3 h).

[0082] 2) The pretreated solid residue was continuously rinsed with deionized water to remove unreacted MoS2 and Na2S2O8 from the filter residue, thus avoiding their impact on subsequent enzymatic hydrolysis and sample detection. Then, solid-liquid separation was performed by vacuum filtration (a circulating water multi-purpose vacuum pump was used for vacuum filtration, with the solid remaining on the filter membrane and the liquid flowing into the filter flask below). 1 mL of the filtrate was taken for sugar content determination. The obtained solid filter residue was dried at a constant temperature of 65°C until it was completely dry, and then used for subsequent enzymatic hydrolysis and structural characterization.

[0083] Furthermore, the present invention optimizes the above-mentioned raw material dosage, pH value, pretreatment time and other process conditions to obtain a series of optimization results.

[0084] Meanwhile, control experiments were conducted on untreated corn stalks, Na2S2O8 pretreatment alone, MoS2 pretreatment alone, and MoS2 + Na2S2O8 pretreatment.

[0085] 1.2 Enzymatic hydrolysis

[0086] Add 20 mL of 0.05 M citrate-sodium citrate buffer (pH 4.8) to a 50 mL Erlenmeyer flask, then add 0.5 g of the product obtained in step 1.1. Mix well, then add a certain amount of cellulase (25 FPU / g CS) and a certain amount of antibiotic (200 μL, for antibacterial effect to prevent contamination). Place the Erlenmeyer flask in a shaker and enzymatically hydrolyze for 72 h at 50 °C and 180 rpm / min to obtain the reaction solution. After the reaction, take 2 mL of the sample and centrifuge at 12000 rpm / min for 5 min. Collect the supernatant, filter, and analyze the total sugar, reducing sugar, and other corresponding sugar contents using high-performance liquid chromatography (HPLC). The yield determination formula is as follows:

[0087]

[0088]

[0089]

[0090] Meanwhile, under the same treatment conditions, corn stalk raw materials that were not treated with the MoS2 activated persulfate system were enzymatically hydrolyzed as a comparison.

[0091] 1.3 Three-element component analysis

[0092] The components of corn straw raw material, pretreated solids, and washing liquid were determined by high-performance liquid chromatography (HPLC) according to the biomass three-element determination procedure established by the National Renewable Energy Laboratory (NREL) (the determination method is described in HYMAN D, SLUITER A, CROCKER D, et al. Determination of acid-soluble lignin concentration curve by UV-Vis spectroscopy; Laboratory analytical procedure (LAP) [R]. NREL Technical Report NREL / TP-510-42620, 2007, Wood IP, 2014.). The specific steps are as follows:

[0093] 0.3g of corn stalk raw material was dried and placed in a pressure-resistant tube. 3ml of 72% (w / w) H₂SO₄ solution was added, and the mixture was subjected to a first acid hydrolysis at 30℃ for 1 hour to obtain a first acid hydrolysate. During this process, the stalk was stirred every 10 minutes to ensure complete reaction. After the reaction was complete, deionized water was added to dilute the sulfuric acid to a concentration of 4% (w / w), and the mixture was shaken well. A second acid hydrolysis was then performed at 121℃ for 1 hour. After the second hydrolysis, the mixture was filtered to separate the solid and liquid components. The filtrate was analyzed by OD value determination and high-performance liquid chromatography (HPLC). Each experiment was performed in triplicate, and the average value of the results was calculated. Pretreatment only and a control group (pretreatment + enzymatic hydrolysis) were also prepared.

[0094] 1.4 Characterization and analysis of corn straw structure before and after pretreatment

[0095] This experiment used scanning electron microscopy, specific surface area and porosity analysis, infrared spectroscopy, X-ray diffraction and solid-state nuclear magnetic resonance spectroscopy to compare the differences in the physicochemical properties of corn stalks before and after pretreatment.

[0096] 1.4.1 Scanning electron microscopy characterization

[0097] The untreated materials and the pretreated materials under optimized conditions were fixed and sputtered with gold, respectively. Then, the microstructure was observed under different substrates using a scanning electron microscope with an accelerating voltage of 15KV.

[0098] 1.4.2 Characterization of specific surface area and porosity

[0099] The untreated material and the pretreated material under optimized conditions were degassed at a temperature of 180℃. After degassed, the samples were tested accordingly.

[0100] 1.4.3 Infrared Spectroscopic Characterization

[0101] The dried material was mixed and ground with KBr at a ratio of 1:100, and then compressed into tablets. Its structural characteristics were analyzed using Fourier transform infrared spectroscopy. The scanning wavelength range was set to 4000-400 cm⁻¹. -1 4cm resolution -1 The number of scans was 32.

[0102] 1.4.4 X-ray diffraction characterization

[0103] A small amount of material was prepared into a slide and placed in an X-ray diffractometer to determine its crystal structure characteristics. The Cu copper target length was 1.5406 Å, the tube current was 40 mA, and the tube voltage was 40 kV. The diffraction angle 2θ = 5°–50° was used for rotational scanning at a rate of 6° / min and a step size of 0.02°. Crystallinity (CrI%) and crystallinity index (Crystalline portion%) were calculated using the Segal formula (Segal L, Creely J, Martin A, et al. Martin Jr AE, Conrad CM: An empirical method for forestimating the degree of crystallinity of native cellulose using the X-ray diffractometer. 1962.). Specifically, the formulas for calculating crystallinity (CrI%) and crystallinity index (Crystalline portion%) are as follows:

[0104] CrI=(I 002 -I am ) / I 002 *100%

[0105] Crystalline portion = I 002 / (I 002 +I am )*100

[0106] In the formula I 002 Representing the 002 surface peak and 2θ = 22.5°, I am The diffraction intensity is when 2θ = 18°.

[0107] 1.4.5 Solid-state nuclear magnetic resonance spectrum analysis

[0108] Both the untreated material and the pretreated material under optimized conditions were freeze-dried and then analyzed using a solid-state nuclear magnetic resonance spectrometer. Recordings were taken at 100 MHz at 25°C. 12 CN MR spectrum. Probe 7mm, pulse width 90°, contact time 800μs, cross-polarization time 4μs, sampling interval 2.5s.

[0109] 1.5 Analysis of Enzymatic Hydrolysis Products

[0110] The material composition of untreated and pretreated corn stalks under different conditions was analyzed and tested in accordance with the standards specified by the National Renewable Energy Laboratory (NREL).

[0111] The solid components mainly include cellulose, hemicellulose, and lignin (acid-soluble and acid-insoluble lignin); the liquid components mainly include cellobiose, glucose, xylose, and arabinose. The high-performance liquid chromatography (HPLC) conditions were as follows: hydrogen ion exchange column A, Minex hpx-87H; column temperature 65℃; mobile phase 5 mmol / L H₂SO₄; flow rate 0.6 mL / min.

[0112] 1.6 Fermentation of ethanol from enzymatic hydrolysate

[0113] (1) Culture medium preparation

[0114] Culture medium for activating microorganisms: Weigh out 20 g / L glucose, 10 g / L yeast extract and 20 g / L peptone respectively, and sterilize at 120℃ for 20 min.

[0115] Fermentation medium for *Issa mesasura* enzymatic hydrolysate: 3 g / L yeast extract, 0.2 g / L urea, 5 g / L peptone, and 0.1 g / L diammonium hydrogen phosphate are sterilized at 120°C for 20 min. When using, replace the water in the medium with the enzymatic hydrolysate to prepare a liquid culture medium (i.e., a 50 mL total volume of culture medium).

[0116] Fermentation medium for Saccharomyces cerevisiae enzymatic hydrolysate: 8 g / L yeast extract, 3 g / L peptone, 7 g / L potassium dihydrogen phosphate, and 1 g / L magnesium sulfate, sterilized at 120℃ for 20 min. When using, replace the water in the medium with the enzymatic hydrolysate to prepare a culture medium (i.e., liquid medium), with a total volume of 50 mL.

[0117] (2) Microbial activation and fermentation

[0118] The preserved strains were inoculated into the activation medium and incubated at 38°C for 48 hours to complete activation. Then, 10% of the inoculum (mass fraction) was inoculated into the liquid culture medium prepared by fermentation medium, and fermentation of *Issa mesasura* and *Saccharomyces cerevisiae* to produce ethanol was carried out. *Issa mesasura* was incubated in a constant temperature incubator at 37°C for 108 hours, and samples were taken every 12 hours. *Saccharomyces cerevisiae* was incubated in a shaker at 30°C and 220 rpm for 48 hours, and samples were taken every 12 hours.

[0119] In the ethanol fermentation process, the enzymatic hydrolysate pretreated under the optimal conditions of MoS2+Na2S2O8 described in this application was added to the culture medium for ethanol fermentation. At the same time, the enzymatic hydrolysate pretreated under the optimal conditions of the FeOCl / MoS2 pretreatment system described in Chinese patent CN115094105A "Heterogeneous Fenton-like Catalytic System Based on FeOCl / MoS2 and Its Application" was added to the culture medium for ethanol fermentation as a control.

[0120] 1.7 Data Statistical Analysis

[0121] All experiments were repeated three times. Data were expressed as mean ± standard deviation and charts were generated using Excel in conjunction with Origin.

[0122] 2 Results and Discussion

[0123] 2.1 Optimization of Preprocessing Conditions

[0124] 2.1.1 Persulfate screening

[0125] like Figure 1 As shown in Figure A, persulfates were first screened, and sodium persulfate and potassium peroxymonosulfate were selected to react with MoS2 respectively. It was found that the enzymatic hydrolysis efficiency of sodium persulfate after reacting with MoS2 was much higher than that of potassium peroxymonosulfate and untreated persulfate, with an enzymatic hydrolysis efficiency of 93.5%. Therefore, sodium persulfate was selected as the best persulfate.

[0126] 2.1.2 Effect of single treatment conditions on enzymatic hydrolysis efficiency

[0127] Next, we will perform single-factor screening. Figure 1 In B, the pretreatment with MoS2 and Na2S2O8 alone was compared with the pretreatment with both of them combined. It was found that the yield of reducing sugars with both combined was much higher than that with the single pretreatment, which proved that MoS2 can effectively activate Na2S2O8, with extremely high enzymatic hydrolysis efficiency and a reducing sugar yield of 93.5%.

[0128] 2.1.3 Effect of Na₂S₂O₈ concentration on enzymatic hydrolysis efficiency

[0129] Next, the dosage of sodium persulfate was optimized using a gradient method, such as... Figure 1As shown in Figure C, the yield of enzymatically hydrolyzed sugar continuously increases with the increase of sodium persulfate dosage, but stops increasing when the dosage reaches 14 mmol / L. This is because the OO radical in sodium persulfate breaks down during heating, generating sulfate radicals SO42-. - As the dosage increases, more free radicals are generated simultaneously, resulting in an excess of SO4 in the system. - • Produces some SO4 - It can also react with H2O to remove H atoms from H2O and generate hydroxyl radicals ·OH. ·OH has a stronger ability to remove α-H atoms than other electrons. Considering cost and concerns about the effectiveness of enzymatic sugar hydrolysis, 14 mmol / L was chosen as the optimal addition amount.

[0130] 2.1.4 Effect of MoS2 concentration on enzymatic hydrolysis efficiency

[0131] Since pretreating corn stalks to improve enzymatic hydrolysis is feasible, the amount of MoS2 was further optimized based on the reducing sugar yield. Figure 1 As shown in Figure D, the optimal dosage of MoS2 was determined to be 1.25 g / L.

[0132] 2.1.5 Effect of pH on enzymatic hydrolysis efficiency

[0133] like Figure 1 As shown in E, under the same conditions, within the pH range of 3-9, the initial pH yield of reducing sugars was the highest (the solution's pH was measured to be 3). As the pH increased, the yield decreased slightly at pH 5, and then remained essentially constant thereafter. This is because under strongly acidic conditions, the system utilizes SO42-. .- It is the primary oxidizing agent, and when the pH increases, SO42- will appear in the solution. ·- It coexists with HO·. Furthermore, it coexists with SO4· ·- In contrast, HO· exhibits high reactivity with various organic and inorganic species, resulting in lower selectivity and a greater susceptibility to non-target species. Therefore, the reducing sugar yield decreases at pH values ​​higher than the system's optimum. Based on the reducing sugar yield, the optimal pH for this system is 3, meaning the initial pH is the optimum pH.

[0134] 2.1.6 Effect of pretreatment time on enzymatic hydrolysis efficiency

[0135] Under the optimized dosage conditions described above, the correlation between pretreatment time and reducing sugar yield was further evaluated. Figure 1As shown in Figure F, compared with the control group, the reducing sugar yield of corn stalks treated in this system increased with time within 2 hours, but decreased slightly after 2 hours. This indicates that excessively long treatment times have little effect on increasing the reducing sugar yield of corn stalks and may even lead to the consumption of reducing sugars. Therefore, the pretreatment time should be controlled at around 2 hours.

[0136] 2.1.7 Effects of enzyme dosage and solid-liquid ratio on enzymatic hydrolysis efficiency during enzymatic hydrolysis

[0137] Regarding the design of enzyme loading, previously the enzyme loading amount was determined based on the substrate (solid straw) content in the hydrolysate, with a relatively high loading of 25 FPU / g. To reduce enzyme consumption, this experiment attempted to lower the enzyme loading and hydrolysis time. Therefore, the enzyme addition was based on the cellulose content, and the solid-liquid ratio was optimized with corresponding gradients of 2 FPU / g, 4 FPU / g, and 6 FPU / g. During the experiment, samples from each group were taken and measured at 48h, 72h, 96h, and 120h. The results are as follows: Figure 2 As shown, the total reducing sugar yield gradually increases with time; the total reducing sugar yield gradually increases with decreasing solid-liquid ratio; and the total reducing sugar yield gradually increases with increasing enzyme loading. After optimization, it was found that when the enzyme loading was 6 fpu / g (68.2 g / 100 g), it could almost reach the enzymatic sugar content (72.7 g / 100 g) of the solid loading of 25 fpu / g.

[0138] 2.2 Three-element component analysis

[0139] Pretreatment alters the composition of lignocellulose, affecting subsequent enzymatic hydrolysis. Analyzing component changes under different pretreatment conditions helps explore the system's mechanism for promoting enzymatic hydrolysis. Therefore, this invention analyzes the effects of pretreatment on corn stalk composition under all optimized conditions and correlates it with sugar yield, aiming to explore the system's enhanced enzymatic hydrolysis mechanism through component changes. The results are as follows: Figure 1 As shown in Table 1-6.

[0140] The initial straw contained 31.8% cellulose, 21.5% hemicellulose, and 21.6% lignin. However, its reducing sugar yield was extremely low, only 14.6%. Its glucose yield was 19.1%, and its xylose yield was 7.8%. Through initial persulfate screening, it was found that this system primarily removed large amounts of hemicellulose and lignin, while retaining a significant amount of cellulose, and also greatly increased sugar production.

[0141] In optimizing the amounts of sodium persulfate, MoS2, pH, and pretreatment time, it was found that as the conditions approached the optimal level, the removal of hemicellulose and lignin gradually increased, reaching its highest removal rate at the optimal condition, after which the change became insignificant. This indicates that the removal of lignin and hemicellulose is directly related to the enzymatic hydrolysis and saccharification of corn stalks. Furthermore, the loss of cellulose is lower than the loss of hemicellulose and lignin, which is precisely what an ideal pretreatment method aims for. Compared to untreated stalks, this system results in the removal of more hemicellulose and lignin, with a higher absolute loss. Component analysis results show that this pretreatment system has a significant effect on the removal of hemicellulose and lignin from corn stalks, effectively breaking down the entangled structure between lignin and cellulose fibers. Compared to the removal of hemicellulose and lignin, it can more effectively protect cellulose components. Moreover, because the ability of sulfate radicals to capture π electrons is greater than their ability to capture α-H, and lignin contains a benzene ring structure with a large number of π electrons, it preferentially degrades lignin, while simultaneously degrading some cellulose and most hemicellulose through hydrogen abstraction.

[0142] Next, we will further reveal the mechanism by which the pretreatment enhances the enzymatic hydrolysis of corn straw by comparing the changes in physicochemical properties before and after pretreatment. Tables 1 to 6 show that after MoS2-activated persulfate pretreatment, only 26% of hemicellulose and 47.8% of lignin were retained, while 73.4% of cellulose was retained. The glucose yield reached 98.1%, and the xylose yield reached 76.1%.

[0143] Table 1

[0144]

[0145] Table 2

[0146]

[0147] Table 3

[0148]

[0149] Table 4

[0150]

[0151] Table 5

[0152]

[0153] Table 6

[0154]

[0155] 2.3 Analysis of the physical effects of pretreatment on corn straw

[0156] 2.3.1 Appearance Morphology

[0157] Pretreatment can break down the stubborn structure of lignocellulose, change its surface morphology and roughness, thereby increasing carbohydrate exposure and improving enzymatic hydrolysis efficiency. The appearance of pretreated corn stalks is as follows: Figure 3 As shown, Figure 3 These are scanning electron microscope (SEM) images of corn stalks under untreated and optimized conditions. From Figure 3 As can be seen, compared to untreated straw, its surface is relatively dense and smooth, with a clearly visible linear texture structure. This structure hinders the binding of cellulase and carbohydrates, resulting in extremely low enzymatic hydrolysis efficiency. However, after optimal treatment, the original linear texture of the straw almost disappears, forming many voids and cracks, with numerous serrated indentations on the surface, and the straw cracks layer by layer. Pretreatment selectively removes the relatively weaker portions of hemicellulose and lignin without destroying the overall regular structure, resulting in a relatively orderly structural arrangement. This change in structure significantly exposes carbohydrates, thereby significantly improving enzymatic hydrolysis efficiency.

[0158] For this system of conditions, MoS2 can accelerate SO4. - The continuous and efficient generation of SO4 - • It can focus on attacking relatively small components, reducing their residue on the cellulose surface and truly exposing the separated cellulose. Therefore, although the system does not remove more lignin and hemicellulose, nor does it cause significant changes in the overall structure, the enzymatic hydrolysis efficiency is significantly improved.

[0159] 2.3.2 Specific surface area and porosity analysis

[0160] Pretreatment typically creates a microporous structure on the substrate surface, allowing enzymes to more effectively contact carbohydrates and thus significantly improving enzymatic hydrolysis efficiency. Different pretreatment methods alter the specific surface area (SSA), micropore volume (PV), and pore size (PD) of the substrate, thereby affecting the enzymatic hydrolysis of carbohydrates. Table 7 lists the corresponding SSA, PV, and PD data for materials with different pretreatments obtained through physical adsorption testing.

[0161] Table 7

[0162]

[0163] As can be seen from Table 7, for untreated material, the SSA is 1.2805m. 2 / g, while the sample treated under optimal conditions of this system showed a significant increase in SSA (3.7957m). 2 / g). Scanning electron microscopy revealed that the system treatment removed most of the hemicellulose and lignin, creating numerous microporous structures. These pores facilitate substrate-enzyme contact and reaction. The change in PV is likely due to the system treatment largely preserving the substrate structure, thus ensuring the integrity of the pore structure. The increase in PV after treatment increases the exposed area of ​​carbohydrates, thereby improving enzymatic hydrolysis efficiency. PD affects substrate hydrolysis by influencing the enzyme accessibility of carbohydrates. Cellulase has a size of 10 nm; pore sizes larger than 10 nm allow for better enzyme entry and reaction with the substrate. As shown in Table 7, the untreated PD was 5.7641, while the treated sample had a pore size of 10.322, larger than that of cellulase, allowing for more effective enzyme entry and significantly improving hydrolysis efficiency. Therefore, the increases in SSA, PV, and PD are all important factors contributing to the improved hydrolysis efficiency of this system, with the increase in PD likely making a greater contribution.

[0164] 2.4 Analysis of the chemical effects of pretreatment on corn straw

[0165] 2.4.1 Functional group structure

[0166] To further investigate the changes in the chemical structure of the substrate before and after pretreatment, this experiment selected a 4000-500 cm⁻¹ filtration depth. -1 Further analysis of the samples before and after pretreatment was performed using infrared spectroscopy within the specified range. For example... Figure 4 As shown, the sample exhibits multiple strong absorption peaks within the selected wavenumber range, including several characteristic chemical groups representing cellulose, hemicellulose, lignin, and carbohydrates. Specifically, the absorption peaks of the -OH, -OCH3, and -CH2 functional groups in lignocellulose are located at 3300-3500 cm⁻¹, 2919 cm⁻¹, and 2852 cm⁻¹, respectively. -1 1606, 1512, 1462, 836cm -1 This is the main characteristic absorption peak of lignin. 1725 cm⁻¹ -1 The characteristic absorption peaks for the carbonyl group of hemicellulose are 1426, 1375, 1251, and 896 cm⁻¹. -1 This is the characteristic absorption peak of cellulose.

[0167] Depend on Figure 4 It can be seen that the changes in the cellulose absorption peak before and after pretreatment are not significant, indicating that the pretreatment system did not significantly damage the cellulose structure of the corn stalk samples. (1725cm) -1The decrease in absorption peak indicates that a large amount of hemicellulose underwent deacetylation, resulting in the removal of a significant amount of hemicellulose. However, the absorption peak represented by lignin remained largely unchanged before and after pretreatment, suggesting that the bonds of lignin were not significantly disrupted during the treatment. No significant changes were observed in the aforementioned characteristic peaks in the infrared spectrum. This indicates that the pretreatment of this system did not damage the basic substrate framework.

[0168] 2.4.2 Crystallinity

[0169] Pretreatment can cause changes in the crystal structure and crystallinity of cellulose. It is generally believed that the crystallinity (CrI) of biomass primarily affects the enzymatic saccharification efficiency of lignocellulose. Generally, lignocellulose can influence crystallinity, i.e., the content of crystalline cellulose in biomass. XRD analysis of the changes in crystallinity between untreated and treated corn stalks provides reliable information for revealing the pretreatment mechanism. Figure 5 As shown, the untreated sample exhibits a typical cellulose structure. The biomass sample shows a peak at approximately 2θ = 22.2° in the XRD pattern, corresponding to the diffraction plane of cellulose I. Compared to the untreated sample, the treated sample has a narrower and clearer (002) peak, and the peak intensities of both (101) and (002) are significantly enhanced, indicating an increase in the overall crystallinity. However, the positions of the two peaks remain unchanged, and no additional peaks appear, indicating that the pretreatment of this system did not alter the original structure of lignocellulose.

[0170] As a crucial factor influencing enzymatic hydrolysis, the relative crystallinity index of different samples was calculated using a formula, and the results are shown in Table 8. The crystallinity of the original straw was 22.2%, which increased to 50.45% after treatment with this system. This pretreatment may have led to the breakage of glycosidic bonds and hydrogen bonds between molecules in the cellulose macromolecules, resulting in the destruction of some non-cellulose components and increasing the relative proportion of cellulose in the matrix. Simultaneously, this system has the ability to remove amorphous components such as hemicellulose and lignin, but due to the short treatment time, it does not damage the crystalline regions of cellulose. This can be explained by component analysis and scanning electron microscopy. These results indicate that this pretreatment system can complete the pretreatment process in a short time, better preserving the basic structure of lignocellulose, more effectively increasing the exposure of cellulose and its accessibility to enzymes, which is beneficial for improving the subsequent enzymatic hydrolysis effect.

[0171] Table 8

[0172]

[0173] 2.4.3 Solid-state nuclear magnetic resonance analysis

[0174] To further investigate the structural characteristics before and after pretreatment, this experiment further employed solid-state nuclear magnetic resonance analysis to analyze the structural properties of the straw before and after pretreatment. Figure 6 The images show the straw before and after pretreatment. 13 C-NMR spectrum. According to the literature (Wang S, Ouyang X, Wang W, et al. Comparison of ultrasound-assisted Fenton reaction and dilute acid-catalyzed steam explosion pretreatment of corncobs:cellulose characteristics and enzymatic saccharification[J]. Rsc Advances, 2016:10.1039.C6RA13125E.), the carbon signal peaks of lignin mainly appear in two places, namely in the range of 165-110 ppm and 55.6 pm, which represent the aromatic structure and -OCH, respectively. 3 Groups. The signal peaks of cellulose and hemicellulose are mainly concentrated between 110-60 ppm. The peak at 104 ppm is attributed to cellulose C-1. The strong peak at approximately 73 ppm represents the chemical shifts of cellulose C-2, C-3, and C-5. The cellulose C4 signal peak is approximately in the range of 80-90 ppm, with the amorphous structure at 83 ppm and the crystalline structure at 88 ppm. The cellulose C-6 signal peak is located at approximately 62 ppm. The two characteristic peaks of hemicellulose appear at 173 ppm and 21 ppm, respectively, and are attributed to the carboxyl carbon and methyl carbon. Figure 6 As shown, corn stalks before and after treatment retained similar lignin structural features, indicating that some lignin remained after pretreatment. Based on the changes in hemicellulose signal, pretreatment reduced the hemicellulose signal, but these signals did not completely disappear, indicating that while the hemicellulose content decreased, it still existed.

[0175] 2.5 Analysis of Ethanol Fermentation Results

[0176] The results of ethanol fermentation of enzymatic hydrolysate are as follows Figure 7 As shown, within the selected 108-hour fermentation time range, the ethanol content of *Issa mesasura* showed a gradually increasing trend, reaching 20.5 g / L at 108 hours, which was higher than the effect of MoS2-activated FeOCl pretreatment. The trend throughout the 108-hour reaction time was also higher than that of MoS2-activated FeOCl pretreatment.

[0177] The ethanol yield of *Saccharomyces cerevisiae* reached 12.2 g / L within a 48-hour fermentation period, an increase of 82.0% compared to 6.7 g / L achieved by fermentation with MoS2-activated FeOCl enzymatic hydrolysate. Both results also demonstrate the further improvement in ethanol yield after MoS2-activated Na2S2O8 pretreatment. Furthermore, this pretreatment system is simpler and more economical than MoS2-activated FeOCl pretreatment. These results also demonstrate the feasibility of using MoS2-activated sodium persulfate pretreated enzymatic hydrolysate for ethanol fermentation.

[0178] 3. Conclusion

[0179] 1) This invention proposes a MoS2-activated persulfate pretreatment method, which can efficiently improve the enzymatic hydrolysis efficiency of corn straw.

[0180] 2) This invention optimizes pretreatment process parameters to obtain a pretreatment system with extremely high enzymatic hydrolysis efficiency. The optimal pretreatment conditions for the MoS2-activated Na2S2O8 system are: 14 mmol / L Na2S2O8 added to 1.25 g / L MoS2, treated at 120℃ for 2 h, achieving an enzymatic hydrolysis yield of 93.5% and reducing the enzyme loading to 6 FPU / g, significantly lowering costs for industrial applications. Simultaneously, this pretreatment process avoids the drawbacks of traditional homogeneous Fenton pretreatment, such as long reaction time, iron-based sludge generation, H2O2 transport problems, and low enzymatic hydrolysis efficiency. It is a green, economical, efficient, and environmentally friendly pretreatment process. This system also provides a newer option for lignocellulose pretreatment processes.

[0181] 3) Under optimal pretreatment conditions, the total sugar yield from corn stalks was 92.5%. The yield of reducing sugars reached 92.8%, glucose yield reached 96.8%, and xylose yield reached 76.1%.

[0182] 4) MoS2-activated persulfate pretreatment can effectively degrade lignin, while the degradation loss of cellulose and hemicellulose is relatively small. The degradation of lignin breaks down the stubborn structure of lignocellulose, changes the substrate form and crystallinity of cellulose, improves the accessibility of enzymes to carbohydrates, and improves the enzymatic hydrolysis efficiency.

[0183] The method of this invention can be used directly or combined with other physical, chemical, and biological methods to form a more effective pretreatment method. This invention is of great significance for promoting the utilization of renewable resources and establishing a circular economy.

[0184] The above embodiments are illustrative examples of the implementation of the present invention. Although the present invention has been illustrated and described with specific embodiments, it should be understood that the implementation of the present invention is not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention should be considered equivalent substitutions and are included within the protection scope of the present invention.

Claims

1. A method for pretreating lignocellulose raw materials using a MoS2-activated persulfate catalytic system, characterized in that, Includes the following steps: MoS2 and persulfate were mixed and dissolved in water to obtain a mixed solution, which was used as a pretreatment solution. Lignocellulose raw materials were weighed and added to the mixed solution. The treatment time was 30 min to 3 h and the treatment temperature was 80-140℃ to obtain the product. The MoS2-activated persulfate catalytic system is obtained by mixing MoS2 and persulfate and dissolving them in water to obtain a mixed solution. The final concentration of MoS2 in the mixed solution is 0.5-1.5 g / L, and the final concentration of persulfate is 1-16 mM. The pH value of the catalytic system is 2-5. The persulfate is Na2S2O8. The lignocellulose raw material is corn straw.

2. The method according to claim 1, characterized in that, When adding lignocellulose raw materials, add them according to a material-to-liquid ratio of 1g:10~30mL; the volume of the mixed solution is 100-300 mL.

3. A method for promoting the degradation of lignocellulose raw materials using a MoS2-activated persulfate catalytic system, characterized in that, Includes the following steps: (1) Pretreatment: MoS2 and persulfate are mixed and dissolved in water to obtain a mixed solution, which is used as the pretreatment solution. Lignocellulose raw material is weighed and added to the mixed solution. The treatment time is 30 min to 3 h and the treatment temperature is 80-140℃ to obtain the product. (2) Enzymatic hydrolysis: The pretreated lignocellulose raw material is added to a buffer solution at a solid-liquid ratio of 1g:10~50mL, and the pH of the buffer solution is 4~6; lignocellulose degrading enzyme is added, and the mixture is enzymatically hydrolyzed at 40~50℃ for 24~120h to obtain the enzymatic hydrolysate; the amount of lignocellulose degrading enzyme added is 5~40FPU / g lignocellulose raw material; The MoS2-activated persulfate catalytic system is obtained by mixing MoS2 and persulfate and dissolving them in water to obtain a mixed solution. The final concentration of MoS2 in the mixed solution is 0.5-1.5 g / L, and the final concentration of persulfate is 1-16 mM. The pH value of the catalytic system is 2-5. The persulfate is Na2S2O8. The lignocellulose raw material is corn stalk. In step (2), the lignocellulose-degrading enzyme is cellulase.

4. The method according to claim 3, characterized in that, The buffer solution mentioned in step (2) is any one of citrate buffer solution and phosphate buffer solution or a mixture of two in any proportion; the volume of the buffer solution mentioned in step (2) is 5-25 mL.

Citation Information

Patent Citations

  • Heterogeneous Fenton-like catalytic system based on FeOCl / MoS2 and application

    CN115094105A

  • Method for removing butyl p-hydroxybenzoate by activating persulfate with layered MoS2 and application thereof

    CN110217875A